2007
DOI: 10.1007/s10897-006-9085-9
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Towards Genetic Testing: A Two Year Follow‐Up Study in Patients with Asthma, Diabetes Mellitus and Cardiovascular Disease

Abstract: Adequate knowledge and personal attitudes towards DNA-testing are major determinants of optimal utilization of genetic testing. This study aims to (1) assess the genetic knowledge and attitude towards genetic testing of patients with asthma, diabetes mellitus type II and cardiovascular diseases, (2) show that factual knowledge mainly relates to associations between genes and diseases, less is known on associations between genes, chromosomes, cells and body. The perceived knowledge on DNA-testing has not incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
79
6
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(100 citation statements)
references
References 15 publications
14
79
6
1
Order By: Relevance
“…Moreover, the correct pre-visit knowledge of breast cancer and heredity was 4.8 (CI 4.5-5.1) in the prior study and was 4.7 in the dataset of the current study at the UMCU (Albada 2011). This finding is consistent with studies of cancer patients' reporting that their genetic knowledge did not increase over time (Calsbeek et al 2007). Thus, a comparison of two studies from one genetics centre indicates that characteristics of the population of counselees have not changed much from 2005 to 2009.…”
Section: Limitationssupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the correct pre-visit knowledge of breast cancer and heredity was 4.8 (CI 4.5-5.1) in the prior study and was 4.7 in the dataset of the current study at the UMCU (Albada 2011). This finding is consistent with studies of cancer patients' reporting that their genetic knowledge did not increase over time (Calsbeek et al 2007). Thus, a comparison of two studies from one genetics centre indicates that characteristics of the population of counselees have not changed much from 2005 to 2009.…”
Section: Limitationssupporting
confidence: 91%
“…Many expect to be offered a DNA-test independent of their disease status and risk profile (Metcalfe et al 2007;Hallowell et al 1997;Pieterse et al 2005c). Also, many people in the UK and the NL lack basic genetic knowledge (Henneman et al 2004;Calsbeek et al 2007;Morren et al 2007;Mesters et al 2005;Walter et al 2004). Thus, both UK and Dutch counselees have important information needs and seem to lack genetic knowledge upon entering breast cancer genetic counselling.…”
Section: Introductionmentioning
confidence: 99%
“…For example, 92% indicated that they agreed or strongly agreed with the use of DNA testing for early detection of diseases. Participants in our study had significantly more positive attitudes than those in the two European studies of patient populations that used the same survey instrument ( Jallinoja and Aro, 1999;Calsbeek et al, 2007) ( p < 0.003).…”
Section: Interest and Attitudes Toward Geneticsmentioning
confidence: 53%
“…The number of genes has changed for each survey to reflect current knowledge. Jallinoja and Aro (1999) originally listed 70,000 genes, Calsbeek et al (2007) listed 30,000, and this survey listed 22,000.…”
Section: Perceived Genetic Knowledgementioning
confidence: 97%
See 1 more Smart Citation